Derivation of nominal verbs with the suffix -(i)auti, that belong to the categorial value ʿto be something/ someone or such as what is denoted by the base word’ - Gaidienė, Anželika (Lietuvių kalba, 2012)
The article deals with nominal verbs with the suffix -(i)auti that have common categorical meaning ‘to be something/someone or such as what is denoted by the base word.' The object of the research consists of 239 verbs found in the electronic Dictionary of the Contemporary Lithuanian Language and 236 corresponding verbs from the electronic version of the Dictionary of the Lithuanian Language. According to the derivational meaning (darybos reikšmė), the verbs under investigation are classified into two groups: 1) verbs that mean ‘to be what is denoted by the base word' (they constitute 83% of all verbs that are analysed here) and 2) verbs, meaning ‘to be such as denoted by the base word' (17%). The verbs of the first category are further subdivided into four subclasses: 1) ‘to be someone denoted by the base word (not in the sense of work)' (they make up 69% of all the verbs of the first group), 2) ‘to work as what is denoted by the base word' (25%), 3) ‘to behave as behaves a person or another living being denoted by the base word' (5%) and 4) verbs denoting ‘states, processes that arise from the thing denoted by the base word' (only 1%).The derivatives of these subclasses are further divided according to the part of speech of the base words (nouns, adjectives or numerals) and the type of derivation (simple forms or derivatives: suffix, prefix, inflection or compounds). The investigation carried out has demonstrated that the verbs derived from nominals by adding the suffix -(i)auti which belong to the category meanings ‘to be something/someone or such as what is denoted by the base word' in standard language have few suffix and stem variants, they are not very characteristic of root vowel and consonant change, their base words do not vary a lot.
Keywords: none